2017
DOI: 10.1186/s13075-016-1216-6
|View full text |Cite
|
Sign up to set email alerts
|

CD14brightCD16+ intermediate monocytes are induced by interleukin-10 and positively correlate with disease activity in rheumatoid arthritis

Abstract: BackgroundThree different subsets of circulating human monocytes, CD14brightCD16- (classical), CD14brightCD16+ (intermediate), and CD14dimCD16+ (non-classical) have been recently identified. It has been reported that CD14brightCD16+ monocytes are increased in rheumatoid arthritis (RA). However, the role of each monocyte subset in the pathogenesis of RA is still unclear. The purpose of this study was to investigate the association of CD14brightCD16+ monocytes with RA.MethodsThe study enrolled 35 patients with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 29 publications
12
58
1
Order By: Relevance
“…Besides, a higher percentage of CD16+ intermediate and non-classical monocytes with a pro-inflammatory phenotype has been described in patients with MS [34], neuromyelitis optica [36], RA [18], SLE [37], ANCA-vasculitis [38], sarcoidosis [39], IgA nephropathy [40], JIA with enthesitis [35], type 1 diabetes mellitus [41], thromboembolism [42], atherosclerosis and stroke [43] which is according to our results. Also, we found that the absolute number of classical monocytes inversely correlated with the disease activity (MYOACT and MITAX), which is according with previous data in patients with RA, where there is a higher percentage of intermediate monocytes during disease activity and a higher proportion of classical monocytes during remission [44]. Our data confirm that a differential proportion of monocytes is found in subjects with autoimmune pathologies, according to disease activity.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, a higher percentage of CD16+ intermediate and non-classical monocytes with a pro-inflammatory phenotype has been described in patients with MS [34], neuromyelitis optica [36], RA [18], SLE [37], ANCA-vasculitis [38], sarcoidosis [39], IgA nephropathy [40], JIA with enthesitis [35], type 1 diabetes mellitus [41], thromboembolism [42], atherosclerosis and stroke [43] which is according to our results. Also, we found that the absolute number of classical monocytes inversely correlated with the disease activity (MYOACT and MITAX), which is according with previous data in patients with RA, where there is a higher percentage of intermediate monocytes during disease activity and a higher proportion of classical monocytes during remission [44]. Our data confirm that a differential proportion of monocytes is found in subjects with autoimmune pathologies, according to disease activity.…”
Section: Discussionsupporting
confidence: 91%
“…The differences relate to, among others, the degree of expression of HLA-DR, CD86 and CD1d, which determine their ability to present antigens [8]. Furthermore, the CD14 ++ CD16 + intermediate monocytes have a high expression of CD163 molecule [14] that inhibits activation and proliferation of T cells [27]. It is also a specific marker of monocytes/macrophages exhibiting strong anti-inflammatory properties [28].…”
Section: Discussionmentioning
confidence: 99%
“…All monocytes can secrete proinflammatory cytokines but classical and intermediate monocytes are the most potent producers, while non‐classical monocytes mainly perform immunosurveillance in blood and tissues . Intermediate monocytes are expanded in the circulation of patients with infections, autoimmune, and inflammatory diseases including sarcoidosis . However, respiratory monocytes are less studied and it remains to be elucidated if intermediate monocytes also expand in the lungs of sarcoidosis patients and whether monocytes and DCs contribute to cytokine‐mediated granuloma formation similar to AMs .…”
Section: Introductionmentioning
confidence: 99%
“…9 Intermediate monocytes are expanded in the circulation of patients with infections, autoimmune, and inflammatory diseases including sarcoidosis. [10][11][12] However, respiratory monocytes are less studied and it remains to be elucidated if intermediate monocytes also expand in the lungs of sarcoidosis patients and whether monocytes and DCs contribute to cytokine-mediated granuloma formation similar to AMs. 13 DCs, in particular CD1c + MDCs, potently present antigen to and activate CD4 T cells that drive disease, 14,15 while CD141 + MDCs are superior at cross-presentation to CD8 T cells.…”
Section: Introductionmentioning
confidence: 99%